2013
DOI: 10.1017/s0022215112003234
|View full text |Cite
|
Sign up to set email alerts
|

Morphological consequences of lateral outfracture of the inferior turbinate

Abstract: Lateral outfracture of the inferior turbinate produces varied and inconsistent changes in morphology which may affect the shape, size and position of the turbinate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Several studies have investigated surgical outcomes using patient‐reported subjective scales or objective measures of airflow, but few studies have quantified the postsurgery IT morphology and its relationship to clinical outcomes . Hanna and colleagues reported that lateral outfracture of the IT resulted in inconsistent morphological changes affecting the IT shape, size, and position. Larrabee and Kacker reviewed level 1 evidence studies (prospective, randomized trials) and concluded that, due to the lack of randomized trials comparing multiple surgical techniques, no surgical technique can be decisively selected as the best at reducing symptoms of nasal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated surgical outcomes using patient‐reported subjective scales or objective measures of airflow, but few studies have quantified the postsurgery IT morphology and its relationship to clinical outcomes . Hanna and colleagues reported that lateral outfracture of the IT resulted in inconsistent morphological changes affecting the IT shape, size, and position. Larrabee and Kacker reviewed level 1 evidence studies (prospective, randomized trials) and concluded that, due to the lack of randomized trials comparing multiple surgical techniques, no surgical technique can be decisively selected as the best at reducing symptoms of nasal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…They found a significant reduction in the angle and the distance between the IT bone and the lateral wall of the nasal fossa and the area lateral to the IT bone 1 and 6 months following surgery. However, Hanna et al . recently showed that lateral outfracture of the IT produced varied and inconsistent results, depending on the shape, size, and position of the IT.…”
Section: Discussionmentioning
confidence: 99%